Dipyridamole increases red cell deformability. - Sowemimo-Coker, S O (1983)
The effects of dipyridamole on red cell filterability both in vitro and ex vivo were measured. In a balanced, randomised and double-blind trial, six healthy male and female volunteers (22-37 years) were given dipyridamole 400 mg/day or matching placebo in four divided doses for 3 days, and heparinised venous blood samples were taken 1 h after the ingestion of the last dose. Filterability of red cells was increased significantly (P less than 0.05 paired t-test) when the subjects were on dipyridamole compared with placebo. In separate experiments, 15 min incubation with 2 or 20 micrograms/ml dipyridamole in vitro was found to have no effect on the filterability of freshly prepared red cell suspensions. After 24 h storage at 4 degrees C, the filterability of red cells was significantly decreased (P less than 0.01) and this could be partially prevented by adding dipyridamole to the stored cells (P less than 0.05). These results suggest that dipyridamole has an effect on the behaviour of the red cell membrane to increase the deformability of the cells. This may contribute to its therapeutic effect.